Did the US Shale Oil Revolution Ruin Oil Industry Stock Market Returns? - Barrows, Samuel D. (International Journal of Energy Economics and Policy, 2020)
The stock market performance of the US oil industry is evaluated against a combination of benchmarks before and after the US shale oil revolution, in order to ascertain whether the increase in US shale oil production had an adverse impact on oil industry stock market returns. In 2014, the dynamic of the global crude oil supply-demand situation was such that the oil price fell because of the increased US crude oil production. Saudi Arabia and the other major producers preferred to have low oil prices, at least temporarily, in order to penalize the US shale oil players. Any oil price increase since then is seen as leading to an increase in US crude oil supply which then further reduces oil prices. The oil industry outperformed the benchmarks prior to the ramp up of US crude oil production led by the shale oil revolution, but the industry underperformed the benchmarks after these production increases. Hence, the US shale oil revolution did ruin the oil industry stock market returns. Several topics for discussion are included: The US Shale Oil Revolution; World Crude Oil Markets; Crude Oil Price Dynamics in the US; and Crude Oil Price Impacts on Oil Companies. Keywords: Shale Oil Revolution, Crude Oil Price, Oil and Gas Industry, Stock Market Returns JEL Classifications: Q32, Q41, Q43 DOI: https://doi.org/10.32479/ijeep.9171